(untitled) (Jurnal Bahasa, 2006)
Terminology can be categorized under the umbrella of lexicography. The distinctive feature between the two is the level of specificity described in each area. The formation of Majlis Bahasa Brunei, Indonesia dan Malaysia (MABBIM) has successfully create millions of terminologies that are being agreed upon and this has in turn enhanced the understanding between the countries involved. However, differences in terminologies between Malay and Indonesia continue to exist and in fact have become wider. There are four categories that have been agreed upon and they are first, total similarity (e.g.: kekurangan penduduk); second, terms that have been agreed upon but differ partially (e.g.: nomor and nombor); third, terms that are synonymous with at least one other country (e.g.: alat/instrumen for In-donesia and only slat for Malaysia); and lastly terms that are totally different in each country (e.g.: batas kota for Indonesia and sempadan Bandar). In addition, both countries decided to dismiss any terminologies that are totally different and incomprehensible. This paper aims to explain the occurrence of this phenomenon. Linguistics knowledge enables language users to understand that theses differences are due to history, culture and demographic factors.